The Effect of Group Counseling Toward Self Esteem of HIV/AIDS Sufferer Female Inmates in Pekanbaru Woman Correctional Institution - Yakub, Elni; Saam, Zulfan; Nopriani, Annisa (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The prison environment is an uncomfortable for prisoners because lifes activity is limited to the walls of prison buildings. To be prisoner is a source of stress. The purpose of this study was to describe the life history of female prisoners of HIV / AIDS sufferer and the influence of counseling on their self-esteem. The subjects in this research were five female prisoners who had HIV / AIDS. Treatment given by group counseling. Analysis data use qualitative method. The result of the research is as follows, Marriage status, all subject status in this research is widow. Two subjects are infected HIV / AIDS virus from their boyfriend, one person from husband and two infected by drug injection. Group counseling have a positive effect to increase self esteem of female inmates. All subjects realize that they will be accepted in their family (parents, siblings and children). They made a pledge to will not repeat the misuse of drugs when they are released. After exiting the prison they will be a tailor, continue the salon business, and make a snack for bussines.